PEMBENTUKAN KATA DAN ISTILAH BARU DALAM BAHASA ARAB MODERN - Syamsul Hadi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
This paper is aimed to discuss how to produce new words and terms in Modern Standard Arabic (MSA). Due to the development of Science, Technology, and Arts, new words and terms are born. Because the new words and terms are derived from foreign languages, especially English, some methods of formation in Arabic language are needed. There are (5) five methods of this formation. Firstly, Qiyas; the use of analogy in producing new words and terms based on the Arabic rules. Secondly, isytiqaq; the use of old Arabic form to produce a new words and terms. Thirdly, translation of foreign language to Arabic. Fourtly, borrowing from foreign languages which have two categories; ta`rib (fully Arabization) and tadkhil (borrowing). Fiftly, acronym/abbreviation which is newly used in Arabic language.